Essentials of Epidemiology in Public Health - Christian T. K.-H. Stadtlander (Epidemiology, Biostatistics and Public Health)
Review of: Essentials of Epidemiology in Public Health. Ann Aschengrau and George R. Seage III. Burlington, MA: Jones and Bartlett Learning, 2014, 534 pp., $111.95. ISBN: 978-1-284-02891-1